From Shame to Self-acceptance: A Hermenetuic Literature Review - Greenwood, Bogumila (Auckland University of Technology, 2016)
This dissertation is a hermeneutic literature review of the dialectic of shame and self-acceptance, and how it informs the concept of self-acceptance as the goal of psychodynamic treatment. The dissertation’s inception was inspired by the quotation from McWilliams (2004): “Self-knowledge is one goal of psychoanalytic treatment, but a more profound goal is self-acceptance. The more one accepts aspects of the self that have been seen as shameful, the less one is controlled by them” (p. 137). The context of hermeneutics of trust as conceptualised by Orange (2011) provided the framework of a new, more accepting approach to the suffering stranger. During my exploration of the psychodynamic literature the themes of shame, gaze and self-acceptance emerged as leading the inquiry. The intersubjective perspective informed the exploration of shame and acceptance as relationally engendered and maintained affects. The concept of gaze functioned in this study as an experiential bridge between the states of being hidden and being seen, and at the same time I consider gaze as a milieu of the dialectical dance of shame and self-acceptance. This research became a personal journey of discovering my shame and it lead me to a deeper understanding of the McWilliams’ quotation. Shame is an universally experienced affect and is present throughout the psychotherapeutic process. The awareness of it, and the therapist’s connection to his own shame, may be helpful in embracing shame and working with it. As a result, the patient is offered a new experience of being gazed upon by the accepting therapist, and given an opportunity to self-reflect with an acceptance of those aspects of themselves that may have been seen as shaming. Self-knowledge has always been considered as an important goal of therapy, but self-acceptance is posited as a more profound goal of psychodynamic treatment. Self-acceptance is understood as self-reflection on aspects of oneself that may never change; which, as a result of therapy that has reached its goal, are not seen as shameful any more.
Keywords: Shame; Self-acceptance; Gaze; Goal of therapy